Exploration of the "Integration Education" system in the "New Liberal Arts" of Zhejiang University of Applied Sciences - Jing, Luo; Tan, Zhao Shu (International Journal of Scientific Research and Management (IJSRM), 2024)
The local application-oriented undergraduate colleges in Zhejiang Province echo the construction of new liberal arts in the practice of "integration of art and industry" and "integration of production and education" in clothing design education. This article focuses on the exploration and practice of the new liberal arts model of clothing design education, shifting from "subject-oriented" to "demand-oriented," aiming to adapt to the development of the times and serve the transformation and upgrading of regional industrial economy.It explores the theoretical logic and practical orientation of the new liberal arts in clothing design education under the driving force of science and technology and value guidance.Based on the development of clothing industry in Haining City, Jiaxing City and the current situation of application-oriented undergraduate colleges in clothing design education, the study focuses on the integration of disciplines and the collaborative education mechanism of production and education from the perspectives of "locality" and "application-oriented". Integrating the advantages of local clothing industry and cultural characteristics into teaching projects to activate the regional radiation role of local colleges. By carrying out the integration education of "new liberal arts" under the principle of "upholding the tradition and innovating", a cultural ecology for ensuring the quality of clothing design talent cultivation is created.